STRATEGIES IN ENHANCING THE QUALITYSERVICES OF TRAFFIC SPECIAL DIVISION - Yuliantini Yuliantini; Fachry Azhar; Wynd Rizaldy (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2015)
The purpose of this research is to find out the strategies in enhancing the quality of services of PT. SchenkerPetrologUtama which is focused on cargo handling. This research is using SWOT analysis to find out the internal and external factors of PT. Schenker. They are the company’s good image, good relations with the customers, owned-vast capacity warehouse, insurance-sent goods, and the company’s well-documented shipment. On the other hand, it is also found that the company has some weaknesses such as lack of transport owned by the vendor, lack of supervised-material system, undetailed-packing process, less communication and coordination between branches and the minimum number of vendors. The external factors start with the opportunity owns by PT. Schenker which are the vast developing of delivery services, the varieties of exhibition and other events, the fast growing business of technology and information, joining other companies’ tender, and the increasing number of local mover companies. However, PT. Schenker also has some threats due to the fast growing of other cargo handling companies, the movement of employees to other division, the disloyal vendors, the time constraints in sending goods, and the consequences (delay) met in Customs and Immigrations. Based on the quadrant, the proposed strategies should be used by the company are aggressive and intensive. They are market expansions, market and product development.